Stopping Winter Flooding of Rice Fields to Control Invasive Snails Has no Effect on Waterbird Abundance at the Landscape Scale - Bernardo-Madrid, Rubén; Vera, Pablo; Gallardo, Belinda; Vilà, Montserrat (Frontiers in Ecology and Evolution, 2022)
The invasive apple snail (Pomacea maculata) appeared in 2010 in the Ebro Delta Natural Park, an important area for rice production and waterbird conservation in the eastern Mediterranean. To control crop damage, farmers stopped flooding their rice fields in winter, an agri-environmental scheme (AES) applied for more than 20 years in some European and American regions to favor flora and fauna from wetlands, including wintering waterbirds. Thus, apple snail control is controversial because of its potential side effects on international waterbird conservation efforts. Despite the fact that 10 years have passed since the first flooding limitations, and the alarms raised by the managers of the Natural Park, the side effects of apple snail management on waterbird conservation have not been evaluated. Here we fill this gap by analyzing a 35-year time series to assess whether abundance trends of 27 waterbird species, from five functional groups, decreased in the Ebro Delta after stopping winter flooding. We considered the effects of confounding local factors by also assessing trend changes in l'Albufera, a similar nearby not invaded wetland where flooding has not been interrupted. In addition, as a control of the positive effect of winter flooding, we also assessed whether abundance trends increased in both wetlands after applying this AES winter flooding. Our results showed complex and decoupled trend changes across species and geographical areas, without statistical evidences, in general or for any particular functional group, on the positive effect of winter flooding in both wetlands neither on the negative effect of its cessation in Ebro Delta. These results suggest the safety of this apple snail control in terms of waterbird abundance at a landscape scale. In addition, these results question, at least in two important wintering areas in Europe, the attractor role associated with the flooding agri-environmental scheme applied for decades.